The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/atm.atm_396_16
|View full text |Cite
|
Sign up to set email alerts
|

What should be the appropriate minimal duration for patient examination and evaluation in pulmonary outpatient clinics?

Abstract: INTRODUCTION:Patient examinations performed in a limited time period may lead to impairment in patient and physician relationship, defective and erroneous diagnosis, inappropriate prescriptions, less common use of preventive medicine practices, poor patient satisfaction, and increased violent acts against health-care staff.OBJECTIVE:This study aimed to determine the appropriate minimal duration of patient examination in the pulmonary practice.METHODS:A total of 49 researchers from ten different study groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The workload was particularly higher in state hospitals. A recent study by Musellim et al, 18 however, suggested that in pulmonary practice, the average time allocated to each patient should be 20 minutes and that physicians should spare 25 minutes for patients with chronic lung disorders. In reality, however, under time constraints for each patient, physicians appear to depend more heavily on their clinical experience and possibly use preconceived templates in the evaluation and management of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The workload was particularly higher in state hospitals. A recent study by Musellim et al, 18 however, suggested that in pulmonary practice, the average time allocated to each patient should be 20 minutes and that physicians should spare 25 minutes for patients with chronic lung disorders. In reality, however, under time constraints for each patient, physicians appear to depend more heavily on their clinical experience and possibly use preconceived templates in the evaluation and management of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The collection of medical history has been addressed as the longest part of the medical evaluation, with a mean duration of 5-36.6 minutes. 16 The median duration of the initial VCC in the recent study was 16 (12–21) minutes. As the diagnostic spectrum in general pulmonology practice is quite broad, the needed time may be longer than that of a recent study.…”
Section: Discussionmentioning
confidence: 98%
“…The steady growth in the Turkish population puts ever-increasing strain on its limited budget health. In a recent work from Turkey, it was reported that the hospitals run by the Ministry of Health in Turkey allocate doctor appointments for every 7.5 min underlying the strain on the system, providers, and patients [7]. As such, Turkey’s population density will guide policy makers toward more innovative care models (Fig.…”
Section: Introductionmentioning
confidence: 99%